ANALISIS PENGARUH BRAND IMAGE DAN SERVICE QUALITY TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN PADA E-COMMERCE TOKOPEDIA - Annisa Effendi (2022)
This research was conducted to analyze and study the influence of Brand Image and Service Quality on customer loyalty through customer satisfaction on Tokopedia e-commerce. This study was conducted with respondents who use the Tokopedia application with a minimum of 3x purchases. Data collection using a questionnaire (gform) and 100 respondents have been collected. This research was conducted in quantitative and descriptive analysis using SmartPLS and the three box method. This research states that (1) Brand Image has a positive and significant effect on customer loyalty on Tokopedia e-commerce. (2) Service Quality has a positive and significant effect on customer loyalty on Tokopedia e-commerce. Good Service Quality will form customer loyalty based on positive experiences received continuously from consumers. (3) Brand Image on customer satisfaction in Tokopedia e-commerce, has a positive and significant effect. (4) Service Quality on customer satisfaction in Tokopedia e-commerce, has a positive and significant effect. (5) Customer satisfaction with customer loyalty in Tokopedia e-commerce, has a positive and significant effect.